2021
DOI: 10.1016/j.stemcr.2021.03.012
|View full text |Cite
|
Sign up to set email alerts
|

3D Image Analysis of the Complete Ventricular-Subventricular Zone Stem Cell Niche Reveals Significant Vasculature Changes and Progenitor Deficits in Males Versus Females with Aging

Abstract: With age, neural stem cell (NSC) function in the adult ventricular-subventricular zone (V-SVZ) declines, reducing memory and cognitive function in males; however, the impact on females is not well understood. To obtain a global view of how age and sex impact the mouse V-SVZ, we constructed 3D montages after multiplex immunostaining, and used computer-based 3D image analysis to quantify data across the entire niche at 2, 18, and 22 months. We discovered dramatic sex differences in the aging of the V-SVZ niche v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Apparently, the addition of Clo predominately contributed to the constriction of the blood vessel. Afterwards, blood flow velocity was locally monitored over time, which was proved to be inversely proportional to the local vascular diameter according to Bernoulli's principle 34 . It was obvious that the blood flow velocity significantly increased by 157.1% (28.17/17.93 cm/s) at 4 h post-injection of Fiber-Rop/Gel-Clo and slightly attenuated at 8 h ( Figure 3 D and 3 E ), compared to the velocity before administration.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the addition of Clo predominately contributed to the constriction of the blood vessel. Afterwards, blood flow velocity was locally monitored over time, which was proved to be inversely proportional to the local vascular diameter according to Bernoulli's principle 34 . It was obvious that the blood flow velocity significantly increased by 157.1% (28.17/17.93 cm/s) at 4 h post-injection of Fiber-Rop/Gel-Clo and slightly attenuated at 8 h ( Figure 3 D and 3 E ), compared to the velocity before administration.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the average distance between clusters and vessels displayed a significant increase with age ( Figure 5 E). However, with age DCX + clusters are less compact (see Figure S1 ) as well as undergoing vasculature structure changes (i.e., diameter, density, and tortuosity) ( Zhao et al., 2021 ), suggesting that the change in distance of clusters and blood vessels is in part due to fewer existing clusters near vessels to facilitate vasophilic migration. We found that a majority of the DCX + neuroblast clusters are within 0–20 μm distance of a blood vessel ( Figure 5 F).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 20, 2023. ; https://doi.org/10.1101/2023.01.18.524632 doi: bioRxiv preprint subventricular zone (V-SVZ), one of the locations in which neural stem cells (NSCs) reside (21,22). Neurogenesis was found to be more prominent in female mice compared to age-matched males with higher proliferating rates and lower numbers of apoptotic cells seen in the V-SVZ of adult mice (22).…”
Section: Discussionmentioning
confidence: 99%